Insecticide seed treatments for managing maggots (Diptera: Anthomyiidae) in onion across selected regions in North America - Leonardo D. Salgado; Alan G. Taylor; Mary Ruth McDonald; Rob G. Wilson; Timothy D. Waters; Josephine B. Antwi; Stuart Reitz; Nathan Hesler; Brian A. Nault (Crop Protection, 2026)

Warming-induced shift in the climate response of Scotland’s temperate rainforests - Charles Norman; Frederick Märker; Alexis Arizpe; Alper Kaan Kadioglu; Zulfiyor Bakhtiyorov; Tatiana Bebchuk; Rob Wilson; Ulf Büntgen (Forest Ecology and Management, 2026)

Applying multi-parameter dating to Scottish historical buildings - Duncan V. Mifsud; Coralie M. Mills; Anne Crone; Rory Abernethy; Emily Reid; Rob Wilson (Dendrochronologia, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Multi-parameter crossdating for sub-fossil and historical samples - Rob Wilson (Dendrochronologia, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Tracing the origins of Stradivari’s resonance wood - Mauro Bernabei; Ilaria Stefani; Ulf Büntgen; Marco Carrer; Paolo Cherubini; Katarina Čufar; Michael Grabner; Frédéric Guibal; Nicola La Porta; Nicoletta Martinelli; Olivia Pignatelli; Klaus Pfeifer; et al. (Dendrochronologia, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Tree-ring blue intensity and climate sensitivity: Exploring site and method-specific variations in southern Yukon, Canada - Yonghong Zheng; Rob Wilson; Mingjun Wang; Emily Reid (Dendrochronologia, 2025)

Exploring potential drivers of divergence in tree-ring based temperature reconstructions of NW North America - Marcel Kunz; Rob Wilson; Emily Reid; Eileen Kuhl; Jan Esper (Dendrochronologia, 2025)

Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.

Impact of pollution on the temperature sensitivity of multiple Norway spruce tree-ring parameters in Central Europe - Yumei Jiang; Krešimir Begović; Martin Lexa; Juliana Nogueira; Georg von Arx; Jan Tumajer; Ryszard Kaczka; Filip Oulehle; Nataliya Korolyova; Jesper Björklund; Kristina Seftigen; Vaclav Treml; et al. (Agricultural and Forest Meteorology, 2025)

Assessing the chemical burden of the North-East Atlantic ecosystem through targeted and untargeted HRMS-based approaches - Georgios Gkotsis; Maria-Christina Nika; Nikiforos Alygizakis; Konstantinos Vasilatos; Antonia Athanasopoulou; Jonathan L. Barber; Rob Berbee; Thierry Burgeot; Susana Galante Oliveira; Johan Gustafsson; Alejandro Iglesias Campos; Ulrike Kammann; et al. (Journal of Hazardous Materials, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Seismic hazard and shifting channels: Exploring coseismic river response - Erin McEwan; Timothy Stahl; Rob Langridge; Tim Davies; Andrew Howell; Matthew Wilson (Earth-Science Reviews, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

A definition and standardised terminology for Blue Intensity from Conifers - Jesper Björklund; Kristina Seftigen; Ryszard J. Kaczka; Miloš Rydval; Rob Wilson (Dendrochronologia, 2024)

Blue intensity measurements in a South American conifer: evaluation of different methodological approaches for Araucaria araucana - Ignacio A. Mundo; Ricardo Villalba; Silvina Velez; Rob Wilson (Dendrochronologia, 2024)

Mission-Oriented Innovation Districts: Towards challenge-led, place-based urban innovation - Sebastian Fastenrath; Sam Tavassoli; Darren Sharp; Rob Raven; Lars Coenen; Bruce Wilson; Daan Schraven (Journal of Cleaner Production, 2023)

Picea schrenkiana tree ring blue intensity reveal recent glacier mass loss in High Mountain Asia is unprecedented within the last four centuries - Weipeng Yue; Kristina Seftigen; Feng Chen; Rob Wilson; Heli Zhang; Yunling Miao; Youping Chen; Xiaoen Zhao (Global and Planetary Change, 2023)

Decline of anthropogenic lead in South Atlantic Ocean surface waters from 1990 to 2011: New constraints from concentration and isotope data - Arianna Olivelli; Katy Murphy; Luke Bridgestock; David J. Wilson; Micha Rijkenberg; Rob Middag; Dominik J. Weiss; Tina van de Flierdt; Mark Rehkämper (Marine Pollution Bulletin, 2023)

Climatic controls on the survival and loss of ancient types of barley on North Atlantic Islands - Peter Martin; Terence A. Brown; Timothy S. George; Björn Gunnarson; Neil J. Loader; Paul Ross; John Wishart; Rob Wilson (Climatic Change, 2023)
For ancient types of barley at sites in the Scottish Isles, Faroes, and Iceland, we calculated minimum temperature requirements for grain production (grain production threshold, GPT) as accumulated degree days over the cropping season. Site suitability for barley from AD 1200 to 2000 was investigated by comparing these thresholds with reconstructions of annual cropping season degree days (CSDD) using temperature and tree-ring data. In Iceland, between AD 1200 and 1500, reconstructed CSDD were more favorable in the southwest (Reykjavik), with fewer years below the GPT, than in the North, East and West, but there were two periods (1340–1389 and 1426–1475) with low average CSDD and several years below the GPT which possibly influenced the abandonment of barley cultivation around this time. Reconstructed CSDD for the Faroes (Tórshavn) had only one year below the GPT, but 15 periods of four or more consecutive years with low CSDD which would have challenged barley cultivation, especially in the thirteenth century. Reconstructed CSDD were highest for the Scottish Isles, allowing a more prominent role of barley in the farming system and economy. Nevertheless, years with poor harvests or famines were common and about half were associated with low CSDD, resulting in a significant temperature link but also demonstrating the important contribution of other factors. Despite frequent unfavorable years in both the Faroes and Scottish Isles, resilient production systems, well-adapted barley strains and socio-economic factors allowed barley cultivation to continue, and some ancient types to survive to the present day.

A preliminary study into the use of tree-ring and foliar geochemistry as bio-indicators for vehicular NO x pollution in Malta - Duncan V. Mifsud; Eva E. Stüeken; Rob J. S. Wilson (Isotopes in Environmental and Health Studies, 2021)

Combining ability analysis of common bean (Phaseolus vulgaris L) genotypes for resistance to bean fly (Ophiomyia spp.), and grain yield and component traits - Wilson Nkhata; Hussein Shimelis; Rob Melis; Rowland Chirwa; Tenyson Mzengeza; Isack Mathew; Admire Shayanowako (Euphytica, 2021)

A Framework for Image-Based Modeling of Acute Myocardial Ischemia Using Intramurally Recorded Extracellular Potentials - Brett M. Burton; Kedar K. Aras; Wilson W. Good; Jess D. Tate; Brian Zenger; Rob S. MacLeod (Annals of Biomedical Engineering, 2018)

Reconstructing 800 years of summer temperatures in Scotland from tree rings - Miloš Rydval; Neil J. Loader; Björn E. Gunnarson; Daniel L. Druckenbrod; Hans W. Linderholm; Steven G. Moreton; Cheryl V. Wood; Rob Wilson (Climate Dynamics, 2017)

The impact of swidden decline on livelihoods and ecosystem services in Southeast Asia: A review of the evidence from 1990 to 2015 - Wolfram H. Dressler; David Wilson; Jessica Clendenning; Rob Cramb; Rodney Keenan; Sango Mahanty; Thilde Bech Bruun; Ole Mertz; Rodel D. Lasco (Ambio, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Characterization of spatial distribution of Tetranychus urticae in peppermint in California and implication for improving sampling plan - Jhalendra P. Rijal; Rob Wilson; Larry D. Godfrey (Experimental and Applied Acarology, 2016)

A millennial long March–July precipitation reconstruction for southern-central England - Rob Wilson; Dan Miles; Neil J. Loader; Tom Melvin; Laura Cunningham; Richard Cooper; Keith Briffa (Climate Dynamics, 2013)

A tree-ring reconstruction of East Anglian (UK) hydroclimate variability over the last millennium - Richard J. Cooper; Thomas M. Melvin; Ian Tyers; Rob J. S. Wilson; Keith R. Briffa (Climate Dynamics, 2013)

The Impact of Industrial SO2 Pollution on North Bohemia Conifers - Miloš Rydval; Rob Wilson (Water, Air, & Soil Pollution, 2012)

An experimental 392-year documentary-based multi-proxy (vine and grain) reconstruction of May-July temperatures for Kőszeg, West-Hungary - Andrea Kiss; Rob Wilson; István Bariska (International Journal of Biometeorology, 2011)

In vitro and in vivo characterisation of a novel c-FLIP-targeted antisense phosphorothioate oligonucleotide - Andrew E. Logan; Timothy R. Wilson; Catherine Fenning; Rob Cummins; Elaine Kay; Patrick G. Johnston; Daniel B. Longley (Apoptosis, 2010)

European temperature records of the past five centuries based on documentary/instrumental information compared to climate simulations - Eduardo Zorita; Anders Moberg; Lotta Leijonhufvud; Rob Wilson; Rudolf Brázdil; Petr Dobrovolný; Jürg Luterbacher; Reinhard Böhm; Christian Pfister; Dirk Riemann; Rüdiger Glaser; Johan Söderberg; et al. (Climatic Change, 2010)

Monthly, seasonal and annual temperature reconstructions for Central Europe derived from documentary evidence and instrumental records since AD 1500 - Petr Dobrovolný; Anders Moberg; Rudolf Brázdil; Christian Pfister; Rüdiger Glaser; Rob Wilson; Aryan van Engelen; Danuta Limanówka; Andrea Kiss; Monika Halíčková; Jarmila Macková; Dirk Riemann; et al. (Climatic Change, 2010)

Five centuries of Stockholm winter/spring temperatures reconstructed from documentary evidence and instrumental observations - Lotta Leijonhufvud; Rob Wilson; Anders Moberg; Johan Söderberg; Dag Retsö; Ulrica Söderlind (Climatic Change, 2010)

Reconstructing ENSO: the influence of method, proxy data, climate forcing and teleconnections - Rob Wilson; Edward Cook; Rosanne D'Arrigo; Nadja Riedwyl; Michael N. Evans; Alexander Tudhope; Rob Allan (Journal of Quaternary Science, 2010)
In this study we compare three newly developed independent NINO3.4 sea surface temperature (SST) reconstructions using data from (1) the central Pacific (corals), (2) the TexMex region of the USA (tree rings) and (3) other regions in the Tropics (corals and an ice core) which are teleconnected with central Pacific SSTs in the 20th century. Although these three reconstructions are strongly calibrated and well verified, inter‐proxy comparison shows a significant weakening in inter‐proxy coherence in the 19th century. This breakdown in common signal could be related to insufficient data, dating errors in some of the proxy records or a breakdown in El Niño–Southern Oscillation's (ENSO's) influence on other regions. However, spectral analysis indicates that each reconstruction portrays ENSO‐like spectral properties. Superposed epoch analysis also shows that each reconstruction shows a generally consistent ‘El Niño‐like’ response to major volcanic events in the following year, while during years T + 4 to T + 7 ‘La Niña‐like’ conditions prevail. These results suggest that each of the series expresses ENSO‐like ‘behaviour’, but this ‘behaviour’ does not appear to be spatially or temporally consistent. This result may reflect published observations that there appear to be distinct ‘types’ of ENSO variability depending on location within the tropical Pacific. Future work must address potential dating issues within some proxies (i.e. sampling of multiple coral heads for one location) as well as assessing the time stability of local climate relationships with central Pacific SSTs. More emphasis is needed on sampling new and extending old coral proxy records from the crucial central and eastern tropical Pacific region. Copyright © 2009 John Wiley & Sons, Ltd. and © Crown Copyright 2009.

Pacific and Indian Ocean climate signals in a tree‐ring record of Java monsoon drought - Rosanne D'Arrigo; Rob Allan; Rob Wilson; Jonathan Palmer; John Sakulich; Jason E. Smerdon; Satria Bijaksana; La Ode Ngkoimani (International Journal of Climatology, 2008)
Extreme climate conditions have dramatic socio‐economic impacts on human populations across the tropics. In Indonesia, severe drought and floods have been associated with El Niño‐Southern Oscillation (ENSO) events that originate in the tropical Indo‐Pacific region. Recently, an Indian Ocean dipole mode (IOD) in sea surface temperature (SST) has been proposed as another potential cause of drought and flood extremes in western Indonesia and elsewhere around the Indian Ocean rim. The nature of such variability and its degree of independence from the ENSO system are topics of recent debate, but understanding is hampered by the scarcity of long instrumental records for the tropics. Here, we describe a tree‐ring reconstruction of the Palmer Drought Severity Index (PDSI) for Java, Indonesia, that preserves a history of ENSO and IOD‐related extremes over the past 217 years. Extreme Javan droughts correspond well to known ENSO and IOD events in recent decades, and most extreme droughts before this recent period can be explained by known ENSO episodes. Coral proxies from regions near or within the two poles of the IOD show good agreement with Javan PDSI extremes over the past ∼150 years. The El Niño of 1877, in conjunction with a positive IOD, was one of the most intense and widespread episodes of the past two centuries, based on instrumental and proxy data from across the tropical Indo‐Pacific and Asian monsoon regions. Although Java droughts typically show the expected association with El Niño‐like conditions and failed Indian monsoons, others (mainly linked to positive IOD conditions) co‐occur with a strengthened Indian monsoon, suggesting linkages between the Indian monsoon, Indonesian drought and Indian Ocean climatic variability. The close associations between the Java PDSI, ENSO and Indian Ocean climate are consistent with the hypothesis that interannual ENSO to decadal ENSO‐like modes interact to generate dipole‐like Indian Ocean variability. Copyright © 2008 Royal Meteorological Society

Testing for tree‐ring divergence in the European Alps - ULF BÜNTGEN; DAVID FRANK; ROB WILSON; MARCO CARRER; CARLO URBINATI; JAN ESPER (Global Change Biology, 2008)
Evidence for reduced sensitivity of tree growth to temperature has been reported from multiple forests along the high northern latitudes. This alleged circumpolar phenomenon described the apparent inability of temperature‐sensitive tree‐ring width and density chronologies to parallel increasing instrumental temperature measurements since the mid‐20th century. In addition to such low‐frequency trend offset, the inability of formerly temperature‐sensitive tree growth to reflect high‐frequency temperature signals in a warming world is indicated at some boreal sites, mainly in Alaska, the Yukon and Siberia. Here, we refer to both of these findings as the ‘divergence problem’ (DP), with their causes and scale being debated. If DP is widespread and the result of climatic forcing, the overall reliability of tree‐ring‐based temperature reconstructions should be questioned. Testing for DP benefits from well‐replicated tree‐ring and instrumental data spanning from the 19th to the 21st century. Here, we present a network of 124 larch and spruce sites across the European Alpine arc. Tree‐ring width chronologies from 40 larch and 24 spruce sites were selected based on their correlation with early (1864–1933) instrumental temperatures to assess their ability of tracking recent (1934–2003) temperature variations. After the tree‐ring series of both species were detrended in a manner that allows low‐frequency variations to be preserved and scaled against summer temperatures, no unusual late 20th century DP is found. Independent tree‐ring width and density evidence for unprecedented late 20th century temperatures with respect to the past millennium further reinforces our results.

El Niño and Indian Ocean influences on Indonesian drought: implications for forecasting rainfall and crop productivity - Rosanne D'Arrigo; Rob Wilson (International Journal of Climatology, 2008)
Indonesia is impacted by severe droughts that cause major food shortages over much of the country, and have long been linked with El Niño events in the tropical Pacific Ocean. Despite seasonal forecasts based on relatively complex climate models, the 1997–1998 ‘El Niño of the century’ was still followed by huge shortfalls in crop production (e.g. a loss of 3 million tons of rice in Java alone), reflecting the large gap that can exist between these forecasts and their actual utilization in agricultural planning. Alternatively, simple predictive models of rainfall and crop yields for Indonesia and other Indian Ocean rim countries have utilized an index of equatorial Pacific sea surface temperatures (Niño‐3.4 SST), and related this index directly to indices of rainfall and crop productivity. However, these latter models have not included climatic information from the Indian Ocean, also implicated as a likely cause of drought in western Indonesia. Here we show that an index of Indian Ocean SSTs, when combined with the previously utilized Niño‐3.4 SSTs, provides a significantly more accurate model of Sept‐Dec drought (PDSI) over Java, Indonesia, than Niño‐3.4 SSTs alone ( ar 2 64.5% vs 37.9%). Based solely on data for the month of August, this model provides the best tradeoff between model skill and adequate lead time for the Sept‐Dec rice planting season. Such simple models can be used to generate readily usable early warning forecasts of drought and crop failure risk in Indonesia, particularly in the western part of the country that is most influenced by Indian Ocean climate variability. Copyright © 2008 Royal Meteorological Society

Cycles and shifts: 1,300 years of multi-decadal temperature variability in the Gulf of Alaska - Rob Wilson; Greg Wiles; Rosanne D’Arrigo; Chris Zweck (Climate Dynamics, 2007)

On the Asian expression of the PDO - Rosanne D'Arrigo; Rob Wilson (International Journal of Climatology, 2006)
The causes and mechanisms of Pacific Decadal Variability (PDV) are still being investigated. One reason that such variability is not better understood is the scarcity of high‐resolution paleoclimatic records from the Asian side of the North Pacific. Here we present a reconstruction of the boreal spring (March–May) Pacific Decadal Oscillation (PDO) index, spanning A.D. 1565–1988, that is the first to represent the large‐scale Asian expression of this phenomenon using tree‐ring data. Intervention analysis reveals significant (95% level) regime shifts corresponding to those in the instrumental PDO during the mid‐1920s, mid‐1940s and mid‐1970s, the latter period associated with the famed 1976 shift in Pacific climate. Shifts in the preinstrumental period show varying correspondence with those of a North American‐based tree‐ring reconstruction of the North Pacific index (NPI), another indicator of Pacific decadal climate variability. Differences between these two time series hint at modulation of local climate from Asian monsoon, El Niño‐Southern Oscillation (ENSO) and volcanic forcing, which could be partly masked by combining data from these sensitive regions in future PDO reconstructions. Overall, however, comparison of the reconstructions from both Asia and North America (NA) is useful for evaluating the distinct expressions of the PDO on both sides of the North Pacific and their interactions with the tropics. Copyright © 2006 Royal Meteorological Society.

Temperature variability over the past millennium inferred from Northwestern Alaska tree rings - Rosanne D’Arrigo; Erika Mashig; David Frank; Rob Wilson; Gordon Jacoby (Climate Dynamics, 2005)

Parallel influence of climate on the behaviour of Pacific killer whales and Atlantic bottlenose dolphins - David Lusseau; Rob Williams; Ben Wilson; Kate Grellier; Tim R. Barton; Philip S. Hammond; Paul M. Thompson (Ecology Letters, 2004)
The grouping behaviour of animals is governed by intrinsic and extrinsic factors which play an important role in shaping their social organization. We investigated the influence of ocean climate variation on the grouping behaviour of two widely separated populations of cetaceans, inhabiting north Atlantic and north Pacific coastal waters. The group size of both bottlenose dolphins in the Moray Firth, UK, and killer whales in Johnstone Strait, Canada, varied from year to year in relation to large‐scale ocean climate variation. Local indices of prey abundance were also related both to climate indices and predator group sizes. The cetaceans tended to live in smaller groups when there was less salmon available in both areas which seem to occur 2 years after a lower phase of the North Atlantic and Pacific Decadal Oscillations. These findings suggest that, even in highly social mammals, climate variation may influence social organization through changes in prey availability.

Temporal instability in tree-growth/climate response in the Lower Bavarian Forest region: implications for dendroclimatic reconstruction - Rob Wilson; Wolfram Elling (Trees, 2004)

Biogeography of Plagiochila (Hepaticae): natural species groups span several floristic kingdoms - Henk Groth; Melanie Lindner; Rosemary Wilson; Florian A. Hartmann; Michaela Schmull; S. Rob Gradstein; Jochen Heinrichs (Journal of Biogeography, 2003)
Aim This paper presents a synthesis of our recent results regarding the biogeography of Plagiochila using a molecular approach, and documents intercontinental ranges within this largest genus of the hepatics. Methods A maximum likelihood analysis of sixty‐one nrITS sequences of Plagiochila was performed and the molecular topology obtained was compared with morphological, phytochemical and geographical data. Results Our molecular data set allowed the identification of eleven Plagiochila sections, the majority of which cover at least two floristic kingdoms. Seven sections have species in Europe (sect. Arrectae , Carringtoniae , Fuscoluteae , Glaucescentes , Plagiochila , Rutilantes , Vagae ). Plagiochila species from Atlantic Europe are usually close to or conspecific with neotropical taxa, whereas species widespread in Europe are closely related to Asian ones and not to those in the Neotropics. Plagiochila sect. Arrectae represents a neotropical – Atlantic European clade. The section is not closely related – as has often been suggested – to the morphologically similar sect. Zonatae from Asia and western North America. Sequence data show that the African P. integerrima and the neotropical P. subplana are members of the Asian sect. Cucullatae (sect. Ciliatae , syn. nov.), which becomes pantropical in distribution. An ITS sequence of P. boryana from Uganda confirms the Afro‐American range of the primarily neotropical sect. Hylacoetes . Similarities in sporophyte morphology between the sect. Cucullatae and sect. Hylacoetes are the result of parallel evolution. Main conclusions Our results indicate that intercontinental ranges at section and species level are common in Plagiochila . Carl's (1931) subdivision of Plagiochila into sections restricted to one floristic kingdom is outdated. Biogeographical patterns in Plagiochila are not dissimilar to those of other groups of bryophytes but elucidation of the geographical ranges of the taxa requires a molecular approach. Contrary to earlier belief, most Plagiochila species from Atlantic Europe do not have close relatives in Asia but are conspecific with or closely related to species from tropical America.